Badania stylów radzenia sobie z szokiem kulturowym w organizacjach - problemy metodologiczne - Łużniak, Magdalena; Witkowski, Stanisław A. (The research on styles of coping with culture shock in organizations - methodological issues, 2006)
This presentation is intended to specify methodological problems of: (a) the description of conceptual facets used to define cross-cultural adaptation, (b) the research based on anthropological, sociological, and psychological theories of cross-culture relations and coping processes as an interdisciplinary framework. This research was supported by a grant from the Polish Ministry of Education, the Council for Scientific Research to Stanisław A. Witkowski and Magdalena Łużniak.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 477-490